The effect of intrauterine human chorionic gonadotrophin injection before embryo transfer on the implantation and pregnancy rate in infertile patients: a retrospective study - Shihabudeen, Thasneem (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: It is known that human chorionic gonadotrophin (hCG) has an important function in angiogenesis and reduces the inflammatory response which in turn favour the implantation process. Human chorionic gonadotrophin is secreted early during the pregnancy, hence plays an important role. Objective of the study is to investigate the effect of intrauterine hCG injection before embryo transfer (ET) on pregnancy outcome in infertile couples. Methods: 100 patients who have undergone embryo transfer from 01 October 2021, to 31 January 2022, in a study setting of ARC Fertility Centre, Saveetha Medical College and Hospital. After ensuring that the patients satisfy the inclusion and exclusion criteria, patients were divided into two groups. Group 1 received intrauterine hCG 5000 IU 3 to 4 hours before embryo transfer. Group 2 control group that did not receive intrauterine hCG. Every patient in either group had been called back on day 15 of embryo transfer to check serum beta hCG. If beta hCG shows a positive result, then primary outcome was positive. Every patient who is pregnancy positive had been called back after 15 days of positive result to see evidence of fetal heartbeat in early obstetrics scan. If fetal heartbeat is present, then secondary outcome was documented. Results: There was significant paired difference in median values of endometrial thickness between day 2 and day on FET and it shows a positive effect on pregnancy results among the hCG group. Conclusions: This study enabled us to determine the effect of intrauterine HCG in improving the success rate of in vitro fertilization (IVF).